EU Civilian Crisis Management The Record So Far - Chivvis, Christopher S. (RAND Corporation, 2010)
The European Union has been deploying civilians in conflict and postconflict stabilization missions since 2003, and the scope of civilian missions is likely to increase in the future. This volume offers a general overview and assessment of the EU's civilian operations to date, as well as a more in-depth look at the two missions in which the EU has worked alongside NATO: Afghanistan and Kosovo.